2019
DOI: 10.7150/jca.30588
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol and Progesterone Induced Differentiation and Increased Stemness Gene Expression of Human Fallopian Tube Epithelial Cells

Abstract: Fallopian tube epithelial cells (FTECs) are thought to be the origin of epithelial ovarian cancer. However, the effect of the hormones on FTECs is unknown, and therefore, this study explored this effect. We successfully derived FTECs from the fallopian tube epithelial layer and treated them with estradiol and progesterone. Reverse transcription polymerase chain reaction was used to evaluate the gene expression of the FTECs' hormone receptors. Confocal and electron microscopy were used to evaluate the morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Yamamoto et al derived FTESC from fallopian tube epithelial cells (FTEC) and proposed the stem cell markers of FTEC as PAX8+, FOXJ1-, and PAX2- [12]; Wang et al found quiescent cell located at distal fallopian tube could be the origin of stem cells that could differentiate into different glandular cells [13]. Our previous study also showed expressions of stemness markers (SSEA3, SSEA4, and ALDH1) and stemness gene expressions (WNT and NOTCH signaling) in FTEC were affected by estradiol and progesterone [14].…”
Section: Introductionmentioning
confidence: 85%
“…Yamamoto et al derived FTESC from fallopian tube epithelial cells (FTEC) and proposed the stem cell markers of FTEC as PAX8+, FOXJ1-, and PAX2- [12]; Wang et al found quiescent cell located at distal fallopian tube could be the origin of stem cells that could differentiate into different glandular cells [13]. Our previous study also showed expressions of stemness markers (SSEA3, SSEA4, and ALDH1) and stemness gene expressions (WNT and NOTCH signaling) in FTEC were affected by estradiol and progesterone [14].…”
Section: Introductionmentioning
confidence: 85%
“…In mouse oviducts, CCs can be rise from NCs under the direction of ovarian steroids [ 67 , 68 ]. As recently seen in bovine, at least seven types of cells at different translational/transcriptional states of ciliogenesis are present in the oviductal epithelium, and their numbers are regulated by the estrous cycle [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…These cells were capable of generating clonally derived organoids that recapitulated the FT epithelial cell content and architecture [ 63 ]. Furthermore, transcript levels of these markers are upregulated by E2 or progesterone treatment in vitro, suggesting hormonal regulation of the stem cell phenotype [ 64 ]. Since fluid flows between intrauterine and pelvic compartments, we can postulate that the FT epithelium, which exists as a continuum of the endometrial luminal epithelium, may contribute to the regeneration of the endometrium and also give rise to ectopic endometriotic lesions through damage or shedding.…”
Section: Tubal Origins Of Endometriosismentioning
confidence: 99%